3D real-time volumetric particle tracking velocimetry – A promising tool for studies of airflow around high-rise buildings. (July 2020) - Zhao, Yu; Ma, Xiaojun; Zhang, Chengbin; Wang, Haoyu; Zhang, Yuanhui
Abstract: Airflow patterns around high-rise buildings affect building wind environment (BWE) including infiltration/exfiltration, heating/cooling loads and internal environment. Scaled high-rise building models are usually placed in a wind tunnel to study BWE. However, measuring 3D flow patterns around scaled high-rise buildings in real-time is a challenge. In this study, a 3D real-time Volumetric Particle Tracking Velocimetry (VPTV) system was used to measure the airflows around three different scaled-building setups: single building, double building parallel to the wind, and double building perpendicular to the wind. Trajectories in Lagrangian coordinates system were tracked and then interpolated to generate 3D Eulerian description of the flow field. In this study, the relative errors of velocities measured by VPTV were smaller than 2% for magnitudes range from 0.025 m/s to 2.2 m/s. The local velocity magnitudes measured by hot-wire anemometer and CFD at selected positions were compared with VPTV measurement with relative error 26.2% and 16.3% respectively. Finally, measured streamlines and reattachment lengths were compared with CFD simulation at selected plane. Results show that the VPTV system is capable of capturing detailed and accurate data of airflow around scaled high-rise building models. Highlights: 3D real-time flow patterns measurement by Volumetric Particle Tracking Velocimetry (VPTV). The VPTV measurement system is calibrated versus known velocity with relative errors of less than 2%. The results of VPTV are compared with that of anemometer measurement and CFD. The flow patterns measured by VPTV can be used for CFD model development and validation.